Human Infection with M- Strain of Brucella canis - Wallach, Jorge Carlos (2004)
The less mucoid strain of Brucella canis or M- strain is used for the serologic diagnosis of canine brucellosis. While this strain is avirulent in dogs, we report the case of clinical brucellosis that developed in a laboratory worker a few days after handling live M- cells for antigen production.